Boundary between multiple sclerosis and neuromyelitis optica. (January 2017) - Nakashima, Ichiro
Abstract: Multiple sclerosis and neuromyelitis optica spectrum disorders are often indistinguishable by their clinical features. Recently, anti‐myelin oligodendrocyte glycoprotein antibody was found in the serum of neuromyelitis optica spectrum disorders patients without anti‐aquaporin‐4 antibody. This finding suggests a new category of central nervous system demyelinating diseases. However, even with the information provided by these serum antibody results, the diagnoses of some patients remain problematic. In the present article, two cases that appeared to be at the boundary between multiple sclerosis and neuromyelitis optica are presented. The first case was a 57‐year‐old woman with past histories of rheumatoid arthritis, myasthenia gravis and idiopathic thrombocytopenic purpura. She developed myelitis after participating in a clinical trial of anti‐BAFF monoclonal antibody and discontinued it. Her brain magnetic resonance imaging showed findings typical of multiple sclerosis, and she was negative for anti‐aquaporin‐4 antibody. Her disease was stabilized after monthly cyclophosphamide pulse therapy. The second case was a 41‐year‐old woman who developed relapsing myelitis. Spinal cord magnetic resonance imaging showed a relatively long lesion. She had not developed brain lesions on routine magnetic resonance imaging for more than 5 years. She was negative for anti‐aquaporin‐4 antibody, and oral prednisolone could not prevent her relapses. However after fingolimod administration, she became stable and Expanded Disability Status Scale gradually improved.